El Patrimonio Cultural Inmaterial Para Generar Un Espacio De Reflexión Social. Estudio De Caso: Comunidad De Nizag, Provincia De Chimborazo, Ecuador - Castillo Ortíz, Daniela Paulina; Salazar, Sandra Patricia Miranda; Merino, Christiam Paúl Aguirre; Pinos, Libeth Lucía Urgiléz (European Scientific Journal, ESJ, 2016)
This case study describes non-tangible elements of the cultural heritage of the community of Nizag, Ecuador. We found a social dynamic built on regional cultural events, including oral traditions and expressions, performing arts, social practices, rituals and festivals, ancestral knowledge of nature and the universe, and traditional artisanship. Linking these categories permitted us to understand intergenerational transmission of heritage and related cultural integrity in this indigenous community. The written record of the living memory of its inhabitants, a heritage registry, allowed the creation of spaces for reflection and self-awareness, reflecting the need to reaffirm the culture and its value for traditional knowledge holders and for new generations, in order to guarantee its reproduction and use for sustainable community tourism. The representativeness of this heritage registry created during community workshops, in part through affirmation of its elements by community members, regained a necessary condition of respect for human rights and diversity among them. Furthermore, the sustainability of tourism involving non-tangible cultural heritage requires putting in place values of equity and solidarity. Making memories more significant, while ensuring their accurate reproduction and enhancing their symbolic value to tourists who visit, not only enriches the experiences of what they share, but also recovers the social and cultural significance of heritage itself.